(untitled) (Research, Society and Development, 2023)
The aim of this work was to analyze the vegetative propagation of Bertholletia excelsa through the mini-cutting technique, with the aid of rhizobacteria mixes. The methodology used was based on the collection of roots of B. excelsa, from which rhizobacteria were bioprospected. From them we formed mixes, for inoculation of mini-cuttings in the plantings in tubes containing commercial substrate, after 90 days they were dug up to collect the data. The experiment was conducted in a completely randomized design, consisting of 6 treatments (5 mixes and controls) with 6 replications, with 1 mini-cutting for each replication. The data were made available in an excel table. The variables analyzed were: survival, callus formation, formation and length of mini-cutting roots. According to MINITAB, the survival of mini-cuttings treated with rhizobacteria x controls presented a significant difference by the KRUSKAL-WALLIS test (p-0.01), for the other variables there was no significant variation. The MAO5PB mix, consisting of MAOPB12A, 12K, 12L, 12J and 12C bacillus, through qualitative analysis, was selected as the most productive and the 5 bacteria that constitute it were molecularly identified: PB12A as Bacillus wiedmannii; 12K as B. paramycoides; 12L as Lysinibacillus fusiformis; 12J as B. paramycoides and 12C as Lysinibacillus fusiformis. This work allows to affirm that it is possible to propagate B. Excelsa through the minicutting technique helped by rhizobacteria and contribute to reduce the pressure in the forest, with recovery of degraded areas, increase commercial production and support small producers in the B. Excelsa wood and nut production chain.